Characterisation of metabolic phenotype in aortic stenosis: insights from a multi-parametric cardiac magnetic resonance study. (3rd October 2022) - Monga, S; Valkovic, L; Mahmod, M; Myerson, S G; Neubauer, S; Rider, O J
Abstract: Introduction: Left ventricular hypertrophy develops in Aortic stenosis (AS) as a result of increased afterload and is related to perturbations in cardiac fatty acid metabolism with evidence of steatosis and impaired myocardial energetics in severe AS. However, there is wide individual heterogeneity when it comes to degree of hypertrophy and progression to myocardial fibrosis and heart failure in those with same degree of stenosis. Underlying interplay of metabolism and hypertrophy may explain this variability. Purpose: We sought to determine if a gradient of myocardial energetic impairment and steatosis exists across the spectrum of AS and precedes irreversible structural remodelling and subclinical LV dysfunction. We investigated metabolic remodelling in AS, focusing on its relationship with stenosis severity, degree of hypertrophy and fibrosis. Methods: 74 AS participants including mild AS (n=18), asymptomatic moderate AS (n=38), asymptomatic severe AS (n=18), and healthy volunteers (n=13) underwent assessment of cardiac function, energetics (myocardial phosphocreatine to adenosine triphosphate ratio, PCr/ATP) and myocardial triglyceride content (MTG) using cardiovascular magnetic resonance (CMR) imaging and spectroscopy. Participants were divided into quartile groups based on their LV wall thickness (LVWT) and peak aortic valve gradient (AVG) to study relationship between cardiac metabolism and hemodynamic markers of LV structure and function. Results: Baseline CMR characteristics (Fig. 1B-C) show a stepwise deterioration in LV structure and function across both the LVWT and AVG quartile groups (p values significant) with high LV mass index and relatively dilated LV as disease severity increases. Cardiac energetics (PCr/ATP]) were reduced in mild-moderate AS, Q2 (1.43±0.13 vs normal controls, Q1 1.80±0.14, p=0.05, Fig.2A) with a progressive decline with increasing AS severity (severe AS, Q4 PCr/ATP 1.39±0.14, p=0.02 vs controls). MTG was elevated in mild-moderate AS, Q2 (1.52±0.84 vs normal, Q1 1.25±0.70%, p=0.032, Fig. 2B). Whilst all AS groups had evidence of subclinical LV dysfunction with impaired strain parameters, impaired systolic longitudinal strain was related to the degree of energetic impairment (R 0.219, p 0.03). In addition, PCr/ATP was strongly associated with the presence of myocardial fibrosis (p 0.01) strengthening the hypothesis that metabolic changes may play a causative role in disease progression (Fig. 2C). Conclusion: A gradient of myocardial energetic deficit and steatosis exists across the spectrum of hypertrophied AS hearts, notably we show in our study that these metabolic changes precede irreversible LV remodelling and subclinical dysfunction. These findings may have value for defining distinct metabolic phenotypes and identifying those most at risk of decompensation. This also opens another avenue for precision metabolic therapy in AS with a potential to intervene and delay or prevent decompensation. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship